Determination of mercury in vegetal tissues by microPIXE: Application to the study of hyperaccumulation by Spirodela intermedia (Lemnaceae) - De La Fournière, Emmanuel M.; Vega, Nahuel Agustín; Müller, Nahuel Agustín; Pizarro, Ramón Augusto; Debray, Mario Ernesto (Sociedad Argentina de Botánica, 2019)
Fil: De La Fournière, Emmanuel M.. Comisión Nacional de Energía Atómica. Centro Atómico Constituyentes. Gerencia de Investigación y Aplicaciones; Argentina. Universidad Nacional de San Martín. Escuela de Ciencia y Tecnología; Argentina